Analysis of marketing efficiency and margin of tomatoes in Sabon Gari LGA, Kaduna State, Nigeria - Makama Saleh Aliyu; Usman Musa Yagba; Magaji Bashiru Dahiru (Indonesian Journal of Agricultural Research, 2025)
The study evaluates the marketing margin and efficiency of tomato marketing in Sabon Gari Local Government Area, Kaduna State, Nigeria, where tomatoes are a crucial agricultural product. Despite being the second-largest tomato producer globally, Nigeria's tomato marketing faces challenges such as seasonality and perishability, with insufficient government support for marketing facilities. It’s against this backdrop that the study attempted to determine the marketing margin and efficiency of tomatoes and to identify the tomato marketing constraints in the study area. A multistage sampling method was used to select the respondents. In the first stage, two vegetable markets were purposefully chosen based on the level of patronage they received. The second stage involved a random selection of 20% of the total traders from a list of traders obtained from their association thus making a total of 100 respondents from the two markets. Data were analyzed using basic statistical techniques viz, mean, percentage, and frequency table. Findings revealed that producers received 96.77% and 94.65% of sales in Samaru and Sabo-Gari markets, while wholesalers and retailers received only 1.09% and 3.31%, respectively. The marketing efficiency was notably higher in Sabon-Gari (114.88%) compared to Samaru (35.66%). Major constraints to tomato marketing were perishability, high input costs, and price swings. To enhance efficiency, the study recommends educating Samaru marketers on value addition and improving logistical support, such as timely input delivery, and better storage and transportation facilities.